Hubungan Penilaian Kerusakan Jalan Metode Bina Marga dan Light Weight Deflectometer (LWD) - Diana, Iffah Lubna; Nurtjahjaningtyas, Indra; Hasanuddin, Akhmad (MEDIA KOMUNIKASI TEKNIK SIPIL, 2024)
The Tegal Siwalan-Banyuanyar Highway in Probolinggo Regency has been damaged at several points and has not received any maintenance for the last 7 years. This has a huge impact on road users because it can interfere with driving comfort and safety, so it is necessary to analyze the road damage that has occurred, including the type of damage and an assessment of road conditions. The Bina Marga method and a light-weight deflectometer (LWD) can be used to assess road deflection in order to assess road condition. The results of this study obtained priority order values for each segment that were in the range 5-11. The greater the value of the Order of Priority obtained, the better the road condition, whereas the smaller the value of the Order of Priority obtained, the worse the road condition. It was also found that the Bina Marga method and the Light Weight Deflectometer (LWD) tool had a poor correlation, so a comparison between the two could not be made for assessing the condition of the road surface layer.